1999
DOI: 10.1038/sj.leu.2401387
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of autologous bone marrow or peripheral blood stem cell transplantation after intensive chemotherapy in myelodysplastic syndromes

Abstract: We prospectively assessed autologous stem cell transplantation for consolidation treatment in a trial of intensive chemotherapy in high risk myelodysplastic syndromes (MDS). In this trial, patients aged 55 years or less with no HLA-identical sibling and achieving CR were scheduled to receive unmanipulated autologous bone marrow transplantation (ABMT) preceded by a consolidation chemotherapy course. Forty-two of the 83 patients aged 55 years or less included in the trial (51%) achieved CR. Three were allografte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 11 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Most patients relapse within the first year, and conventional consolidation chemotherapy does not seem to prolong CR duration (Wattel et al, 1997;Ganser et al, 2000;Hast et al, 2003;Kantarjian et al, 2006b;Hofmann et al, 2007). If there is a potential benefit from autologous stem cell transplantation, this is restricted to younger patients (De Witte et al, 1997;Wattel et al, 1999). This trial is the first to evaluate safety and feasibility of maintenance treatment with azacytidine for patients with highrisk MDS and MDS-AML with CR after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients relapse within the first year, and conventional consolidation chemotherapy does not seem to prolong CR duration (Wattel et al, 1997;Ganser et al, 2000;Hast et al, 2003;Kantarjian et al, 2006b;Hofmann et al, 2007). If there is a potential benefit from autologous stem cell transplantation, this is restricted to younger patients (De Witte et al, 1997;Wattel et al, 1999). This trial is the first to evaluate safety and feasibility of maintenance treatment with azacytidine for patients with highrisk MDS and MDS-AML with CR after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] In a previous study by our group, we analyzed 100 patients in first complete remission who were candidates for SCT. 9,23 The 4-year disease-free survival rates in the donor versus no-donor groups were similar: 31% and 27%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective French study investigated the feasibility of autologous stem cell transplantation after conditioning with busulfan and cyclophosphamide in those patients who achieved a CR after induction chemotherapy, and the study reported about 50% of the patients who were alive 8-55 months after transplantation. 20 More recently, the EORTC presented results from 159 patients with MDS who received a transplant from a HLA-identical sibling or (if not available) an autologous transplantation after induction chemotherapy. The 4-year RFS was 23% for patients with a donor and 22% for patients without a donor (P ¼ 0.7), and the authors concluded that allogeneic and autologous stem cell transplantation result in similar survival rates.…”
Section: Discussionmentioning
confidence: 99%